On the taxonomy of water mites (Acari: Hydrachnidia) described from the Palaearctic, part 2: Hydryphantoidea and Lebertioidea - Sabatino, Antonio Di; Gerecke, Reinhard; Gledhill, Terence; Smit, Harry (Zootaxa, 2009)
The paper explains changes which become necessary in water mite taxonomy after revision of material from museum collections and recent field work. Todothyas Cook, 1974, not Acerbitas Özdikmen, 2006, must replace the preoccupied genus name Thyas Koch, 1836; Acerbitas is ranked as a subgenus of Todothyas. The following synonyms are established: Family Hydryphantidae: Todothyas distincta (Tuzovskij, 2007) = Todothyas colligera (K.Viets, 1923); Todothyas incerta (Lundblad, 1941) = Todothyas barbigera (K.Viets, 1908); Georgella intermedia Walter, 1927 (G. dauphinensis nom. nov. K.O.Viets, 1987) = G. koenikei Maglio, 1906; Hydrobaderia Özkan, 1985 = Hydryphantes Koch, 1841; Hydrobaderia ilicaensis Özkan, 1985 = Hydryphantes crassipalpis Koenike, 1914; Hydryphantes algeriensis Walter, 1925 = H. dispar (Schaub, 1888); Hydryphantes bayeri nonundulatus K. Viets, 1919 = H. planus Thon, 1899; Hydryphantes intermedius Daday, 1901 = H. dispar (Schaub, 1888); Hydryphantes spinipes Walter, 1922 = H. ruber (Geer, 1787); Panisus clypeolatus (Maglio, 1909) = P. torrenticolus Piersig, 1898; Panisus sarasini Bader, 1981 = P. michaeli (Koenike, 1896); Protzia multipora Walter, 1922 = P. squamosa Walter, 1908; Protzia macrognatha Walter, 1944 = P. distincta Walter, 1922; Sindacoides Bader, 1992 = Panisopsis K.Viets, 1926; Sindacoides ticinensis Bader, 1992 = Panisopsis setipes (K.Viets, 1911); Thyasella mandibularis torrenticola Schwoerbel, 1958 = T. mandibularis Lundblad, 1924. Hydryphantes pyrenaicus E. Angelier 1985, published as a nomen nudum, refers to H. armentarius Gerecke, 1996. Family Anisitsiellidae: Bandakia bieberi Bader, 1994 = B. concreta Thor, 1913. Family Oxidae: Oxus koenikei Thor, 1899 = O. longisetus (Berlese, 1885). Family Sperchontidae: Mixosperchon K. Viets, 1926 = Hispidosperchon Thor, 1901; Charoelia Bader, 1988 = Sperchon Kramer, 1877; Charoelia schloethi Bader, 1985 = Sperchon mutilus Koenike, 1908; Sperchon sandozi Bader, 1988 = S. hispidus Koenike, 1895; Sperchon monstruosus Bader, 1957 = S. hibernicus Halbert, 1944; Sperchonopsis phreaticus Biesiadka,1975 = S. procera Láska, 1965 stat. nov. Family Torrenticolidae: Monatractides bicinctus (Láska, 1933), M. parvipalpis (Halbert 1944), M. robustus (Halbert 1944), T. (Monatractides) hibernica Conroy, 1984 = M. madritensis (K. Viets, 1930). Redescriptions are given for numerous further species, redefining diagnostic characters and geographical distributions. Todothyas colligera (K. Viets, 1923) and Wandesia propinqua Walter, 1947 are redefined and newly established as separate species. Parathyas primitiva Lundblad, 1935 is transferred to the genus Todothyas Cook, 1974. Sperchon vaginosus Thor, 1902 is re-established as a distinct species in the ’denticulatus-group’. Torrenticola laskai Di Sabatino spec. nov. is introduced as a new name for Mediterranean populations attributed by several authors to T. lativalvata K. Viets, 1952. Torrenticola amplexa minutivalvata Lundblad, 1956 is elevated to species rank.